Dampak Ex-Dividen Date terhadap Abnormal Return dan Volume Perdagangan Saham pada PeruSahaan LQ-45 yang Terdaftar di BurSa Efek Indonesia Periode 2015-2019 - Sari, Metty Singgar; Utami, Yuni (Konsentrasi: Jurnal Manajemen dan Bisnis, 2021)
This research is a quantitative study with primary data derived from questionnaires. A population of 45 companies, with the sampling technique using purposive sampling technique in order to obtain a sample of 12 companies. The analysis used the Wilcoxon signed Rank Test analysis if the data were not normally distributed and Paired sample T-Test analysis if the data were normally distributed. The results showed that there was a significant difference in abnormal returns between before and after the ex-dividend date, as evidenced by the results obtained by Asymp. sig. (2-tailed) has a value of 0.000 < 0.05, it is concluded that there is an impact of ex-dividend data on abnormal returns for LQ-45 Companies on the Indonesia stock Exchange for the 2015-2019 period. There is a significant difference in stock trading volume between before and after the ex-dividend date, as evidenced by the research results obtained by Asymp. sig. (2-tailed) is worth 0.027 < 0.05, it is concluded that there is an impact of ex-dividend data on the volume of stock trading at LQ-45 Company on the Indonesia stock Exchange for the period 2015-2019. The suggestion of this research is that companies in implementing dividend policy should be based on consideration of the interests of share ownership and also the interests of the company. Dividend policies are important because payments increase the prosperity of shareholders. The behavior of individual investors in making financial decisions is not only influenced by considerations of rationality and objective data. However, it also needs to be influenced by rational actions such as emotions, certain psychological habits and the mood of individual investors to reduce market reactions to the existence of dividend policy.